DIAGNOSTICS AND ELIMINATION OF THE CAUSES OF PSYCHOSOMATIC DISORDERS IN THE WAYS OF PEDAGOGICAL SYSTEM-PARENT APPROACH - Швець, В. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article reveals the main aspects of the behavior of psychosomatic diseases in adolescents and best possible ways to eliminate them through comprehensive and coordinated actions of pedagogical and parent team. Key words: weave therapy, psychosomatic illness, deviant behavior.